Investigating the Perception of Internal Audit in Women's Cooperatives: The Case of Isparta Province - Mahmut Sami Öztürk; Ayşe Gül Gök (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
Today, women's cooperatives, whose numbers are increasing, are among the organizations whose establishments are supported in Turkey. The main subject of our study is to investigate the internal audit perceptions of the partners of women's cooperatives, which have encountered various problems in their operation after their establishment. The study covers women's cooperatives in Isparta center and its surroundings. In this regard, a qualitative research was conducted with women's cooperatives that agreed to participate in the study. Qualitative data obtained with the semi-structured interview form were analyzed with the MAXQDA 2020 program and code schemes were created and interpreted. As a result of the study, it was concluded that the concept and mechanisms of internal audit are not fully known and are not carried out effectively. In addition, it has been concluded that the members do not have full information about the main organs of the cooperative, that cooperatives are generally reluctant to recruit partners, that organ activities generally remain on paper, that risk management is weak, and that there may be erroneous or fraudulent behavior in some cooperatives.